Fertilization and Cleavage Axes Differ In Primates Conceived By Conventional (IVF) Versus Intracytoplasmic Sperm Injection (ICSI) - Calvin R. Simerly; Diana Takahashi; Ethan Jacoby; Carlos Castro; Carrie Hartnett; Laura Hewitson; Christopher Navara; Gerald Schatten (Scientific Reports, 2019)
Abstract With nearly ten million babies conceived globally, using assisted reproductive technologies, fundamental questions remain; e.g., How do the sperm and egg DNA unite? Does ICSI have consequences that IVF does not? Here, pronuclear and mitotic events in nonhuman primate zygotes leading to the establishment of polarity are investigated by multidimensional time-lapse video microscopy and immunocytochemistry. Multiplane videos after ICSI show atypical sperm head displacement beneath the oocyte cortex and eccentric para-tangential pronuclear alignment compared to IVF zygotes. Neither fertilization procedure generates incorporation cones. At first interphase, apposed pronuclei align obliquely to the animal-vegetal axis after ICSI, with asymmetric furrows assembling from the male pronucleus. Furrows form within 30° of the animal pole, but typically, not through the ICSI injection site. Membrane flow drives polar bodies and the ICSI site into the furrow. Mitotic spindle imaging suggests para-tangential pronuclear orientation, which initiates random spindle axes and minimal spindle:cortex interactions. Parthenogenetic pronuclei drift centripetally and assemble astral spindles lacking cortical interactions, leading to random furrows through the animal pole. Conversely, androgenotes display cortex-only pronuclear interactions mimicking ICSI. First cleavage axis determination in primates involves dynamic cortex-microtubule interactions among male pronuclei, centrosomal microtubules, and the animal pole, but not the ICSI site.